Асфальт: роман / Евгений Гришковец - Гришковец Евгений Валерьевич (Махаон, 2011)
Экземпляры: ф. 4 (20120408) / Инвентарный номер: 98447 / Цена: 183.38 / Авт.знак: Г 85 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6